Exploring the Effects of Knowledge about the Internet on Adoption Intentions of Farmers in Punjab, Pakistan: A Behavioral Analysis - Shahzad, A.R.; Akhtar, Noreen; Awan, Kanwal Asghar (Annals of Human and Social Sciences, 2024)
This study goes beyond traditional technology adoption models to explore how farmers’ existing knowledge and internal factors influence agricultural technology adoption among Pakistani farmers by focusing on Internet use. In this study, 416 farmers were randomly selected from five agricultural zones of Punjab province of Pakistan and information about their knowledge and practices was collected. Descriptive and regression analysis revealed that farmers have a good grasp of Internet features, but struggle with advanced skills such as cost reduction, online transactions, and prospecting for new customers. The results of the study show that attitudes alone do not drive behavioral intentions, but rather prior knowledge and internal factors do. Practically, this highlights the need for extension professionals and policy makers to address the Internet skills gap among farmers. Future research should consider additional social factors such as social status and land distribution to better understand Internet adoption behavior.